Android and Laravel-Based M-Petani Application for the West Java Provincial Agricultural Crop Department - Itamar Ferianus Nazara; Ari Purno Wahyu Wibowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The West Java Provincial Agricultural Crop Department faces various challenges in communication and service delivery to farmers, such as a shortage of agricultural extension workers, manual processes for submitting complaints, and inefficient seed request procedures. To address these issues, the M-Petani application was developed, an Android-based solution utilizing web service technology with JSON format for data exchange and integration. This system is designed to deliver agricultural information, facilitate seed requests, and provide a digital platform for submitting complaints. Alpha testing confirmed the application functions in accordance with technical specifications, ensuring secure data validation and storage. Beta testing, conducted with 30 farmers in West Java, demonstrated positive feedback, particularly regarding ease of use, reliability, and user satisfaction. The application enhances communication efficiency, accelerates responses to complaints, and simplifies data management at the Agricultural Crop Department. These results highlight M-Petani as an effective and environmentally friendly digital solution that supports paper reduction and improves service delivery to farmers in West Java.